Antegrade Intentional Laceration of the Anterior Mitral Leaflet to Prevent Left Ventricular Outflow Tract Obstruction: A Simplified Technique From Bench to Bedside. (June 2020) - Lisko, John C.; Greenbaum, Adam B.; Khan, Jaffar M.; Kamioka, Norihiko; Gleason, Patrick T.; Byku, Isida; Condado, Jose F.; Jadue, Andres; Paone, Gaetano; Grubb, Kendra J.; Tiwana, Jasleen; McCabe, James M.; et al.
Abstract : Background: Intentional laceration of the anterior mitral leaflet (LAMPOON) is an effective adjunct to transcatheter mitral valve replacement that prevents left ventricular outflow tract (LVOT) obstruction. To date, LAMPOON has been performed in over 150 patients using a retrograde approach that can be technically challenging. A modified antegrade transseptal technique may simplify the procedure. Methods: Antegrade LAMPOON was developed and tested in nonsurvival pig experiments. Thereafter, antegrade LAMPOON was performed in patients at prohibitive risk of LVOT obstruction. Clinical, procedural, and angiographic details were abstracted from medical records of their index procedure, and were compared with findings in comparable patients at risk of fixed-LVOT obstruction in the LAMPOON investigational device exemption trial. Results: Eight patients at risk of fixed LVOT obstruction underwent antegrade LAMPOON. Leaflet traversal and laceration were technically successful in all. There were no cases of clinically significant LVOT obstruction (mean LVOT gradient at discharge: 5.4±1.4 mm Hg). One patient suffered a ventricular wire perforation, unrelated to the antegrade LAMPOON technique, and did not survive to discharge. At the time of discharge, no patients had an increase of >10 mm Hg in LVOT gradient compared with baseline. Procedure times (from traversal to transcatheter mitral valve replacement) were shorter, compared with the retrograde technique in the LAMPOON investigational device exemption trial (39±09 versus 65±35 minutes). All patients survived (8/8, 100%) the procedure, and 7/8 (88%) survived to 30 days, similar to subjects in the LAMPOON investigational device exemption trial. Conclusions: Antegrade LAMPOON is an effective, reproducible, and simplified strategy to lacerate the anterior leaflet before transcatheter mitral valve replacement. The authors recommend the technique as the new standard for LAMPOON.